Fabrication and characterization of nanostructured ceramic thin films from single source and mixed molecular precursors / Muhammad Ali Ehsan - Ehsan, Muhammad Ali (2014)
This work describes some general procedures for the preparation and characterization of heterobimetallic complexes [Fe2Ti4(μ-O)6(TFA)8(THF)6] (1), [Co2Ti(μ3-O)(TFA)6(THF)3] (2) and a series of metal dithiocarbamate [Bi(S2CNEt2)3]2 (3), [In(S2CNCy2)3]•2py (4), [In(S2CN(iPr)2)3]•1.5py (5), [In(S2CPip)3]•0.5py (6), [In(S2CNBzMe)3] (7), [Ag4{S2CNEt2}3(py)2]n·nNO3·2nH2O (8), [Cd(S2CNCy2)2(py)] (9), [Zn(S2CNCy2)2(py)] (10), [Zn(S2CNBzMe)2(py)] (11), [Pd(S2CNBz2)2]•py (12) [Pd(S2CNCy2)2]•py (13), [Pd(S2CNnHex2)2] (14), [Pd(S2CNCyMe)2] (15) and their disposal for the growth of thin films of ceramic oxide composites and metal sulphides. The physical properties of these complexes have been studied by means of fusion point determination, microanalysis, Fourier transform infrared spectrophotometry (FTIR) and proton nuclear magnetic resonance (1H-NMR) spectroscopy, X-ray single crystal and thermogravimetric and derivative thermogravimetric (TG/DTG) analyses. Thermogravimetric studies prove that all the complexes (1)-(15) undergo facile thermal decomposition at relatively low temperature and are well suited single source precursors for the fabrication of ceramic oxide and sulphide thin films by aerosol assisted chemical vapour deposition. The particle size, phases and crystallinity of the deposited films were determined by X-ray power diffraction (XRPD) while scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectrometry were used for investigating the surface morphologies, crystallite size, shape and elemental compositions. XRPD and EDX analyses revealed the formation of impurity free composite oxides Fe2TiO5-TiO2 and CoTiO3-CoO films at relatively low temperature of 500 °C on glass substrate from precursors (1) and (2) respectively. SEM results showed that fabricated films are crack free, crystalline and possess nanosized features with clear boundaries and architectures. Single source metal dithiocarbamate precursors (3), (4)-(7), (8), (9), (10)-(11) and (12)-(15) have been found suitable for deposition of Bi2S3, β-In2S3, Ag2S, CdS, ZnS and PdS thin films on fluorine doped tin oxide ( FTO) coated conducting glass substrate at temperature range of 300-500 °C and the energy bandgaps (Eg) of the Bi2S3, β-In2S3, Ag2S, CdS, ZnS and PdS thin films determined from UV-Vis spectrophotometry are valued at 1.80, 2.20, 1.05, 2.40, 3.40 and 1.70 eV, respectively, indicating the direct band gap nature of the metal sulphide materials. The photoelectrochemical (PEC) characteristics of the Bi2S3, β-In2S3, CdS, ZnS, PdS and Ag2S thin films electrodes measured from photocurrent potential plot recorded under Air Mass 1.5G illuminations exhibit anodic photocurrent densities of 1.90, 1.25, 1.20, 8.0×10-3 and 4.0×10-3 , 0.22, mA/cm2 at 0.23 and 0.0 V vs. Ag/AgCl, respectively. The photoelectrochemical performances indicate that the newly synthesised precursors are highly advantageous in fabricating metal sulphide electrodes for solar energy harvesting and optoelectronic application.